HUBUNGAN ANTARA REGULASI DIRI DENGAN PROKRASTINASI AKADEMIK PADA MAHASISWA UNIVERSITAS PGRI PALEMBANG - Sujarwo, Sawi (Direktorat Riset dan Pengabdian Masyarakat Universitas Bina Darma Palembang, 2015)
This study aims to determine the relationship between of self regulation with academic procrastination in the student guidance and counseling courses semesters 4 and 6 of PGRI university Palembang. The hypothesis proposed in this study is there a relationship between self regulation with academic procrastination in the student guidance and counseling courses semesters 4 and 6 of PGRI university Palembang. The results by using SPSS version 20.0 showed a correlation coefficient (r) of0,603 with a coefficient of determination (R-square) of 0,364, and p = 0,000 p < 0.01. This suggests that the hypothesis is accepted which showed that there is a significant relationship betweenself regulation with academic procrastination in the student guidance and counseling courses semesters 4 and 6 of PGRI university Palembang